Retrosternal Goiter: 30-Day Morbidity and Mortality in the Transcervical and Transthoracic Approaches. (October 2016) - Khan, Mohemmed N.; Goljo, Erden; Owen, Randall; Park, Richard Chan Woo; Yao, Mike; Miles, Brett A.
Objective: Retrosternal goiters pose a significant challenge in determining the indications and appropriate approach for surgical removal while limiting postoperative morbidity and mortality. The objective of this study is to use the National Surgical Quality Improvement Program (NSQIP) database to compare outcomes of transcervical and transthoracic approaches for retrosternal goiter removal and to review the literature regarding the varying indications for the 2 surgical approaches. Study Design: Administrative database analysis. Setting: NSQIP database. Subjects and Methods: The NSQIP database was queried for all cases of retrosternal thyroid: 2716 patients were included, which represents one of the largest data reviews of patients with retrosternal thyroid pathology who underwent surgery. Data were analyzed to examine morbidity and mortality of the cervical and transthoracic approaches. Results: Patient demographics and preoperative comorbidities were similar between groups. Patients undergoing a transthoracic approach experienced increased rates of unplanned intubations and need for transfusion and length of stay postoperatively. Conclusions: A transthoracic approach is associated with increased rates of several critical postoperative morbidities, and the data indicate the potential of increased overall mortality. Given equivalent retrosternal extension, a transcervical approach should be attempted whenever anatomically possible, regardless of pathology.